Persistent reduction of mucosal‐associated invariant T cells in primary biliary cholangitis. Issue 6 (9th March 2018) - Setsu, Toru; Yamagiwa, Satoshi; Tominaga, Kentaro; Kimura, Naruhiro; Honda, Hiroki; Kamimura, Hiroteru; Tsuchiya, Atsunori; Takamura, Masaaki; Terai, Shuji
Abstract: Background and Aim: Mucosal‐associated invariant T (MAIT) cells constitute a novel subset of innate‐like T lymphocytes characterized by a semi‐invariant T‐cell receptor repertoire capable of recognizing bacterial products. Considering the abundance of MAIT cells in the liver and the possible association between bacterial infections and primary biliary cholangitis (PBC), we aimed to analyze the involvement of MAIT cells in the immunopathogenesis of PBC. Methods: Peripheral blood and liver biopsy specimens were collected from 25 patients with PBC and 19 patients with chronic viral hepatitis. Surgically removed liver tissues distant from tumors in patients with metastatic liver tumors were used as controls. Mononuclear cells were separated using Ficoll gradient, and the expression of various markers was investigated by flow cytometry. Cytokine production was investigated using blood MAIT cells after stimulation by anti‐CD3/CD28‐coupled beads with/without interleukin‐7 (IL‐7). Results: Mucosal‐associated invariant T cells were significantly reduced in both the blood and liver of PBC patients compared with those in controls. MAIT cells in the blood of PBC patients expressed significantly lower levels of activation markers and IL‐7 receptor. Moreover, MAIT cells in the blood of PBC patients showed impaired production of cytokines, especially tumor necrosis factor alpha, after in vitro stimulation with IL‐7. Interestingly, even after biochemical responses were achieved by ursodeoxycholic acid treatment, the frequencies of MAIT cells did not fully recover to normal levels. Conclusions: These findings suggested that MAIT cells were activated, exhausted, and persistently depleted in PBC patients even after ursodeoxycholic acid treatment, possibly as a consequence of persistent liver inflammation.